Assessment variability of annual daily maximum rainfall of Terengganu, Malaysia - Nur Azira Ayuni, Ab Aziz (2015)
Recently, major cities in Terengganu have been affected by problems related to flooding incident. Meanwhile, extreme rainfall during northeast monsoon caused overflowing of Terengganu River and flooding, which cause a lot of destruction of house and property. The main objective of this study is to assess the variability of annual daily maximum rainfall. Tropical Rainfall Measuring Mission (TRMM) satellite-based rainfalls from public domain were used in this study. The daily satellite-based rainfall data for each major cities in Terengganu were retrieved using Geographical Information System (GIS) technique. Gumbel distribution functions were applied to estimate expected return period and probability of extreme rainfall event. For annual daily maximum, the maximum depth at Kemaman, Dungun, Marang, Hulu Terengganu, Kuala Terengganu, Setiu and Besut are 363.96mm 477.54mm, 332.45mm, 303.68mm, 347.85, 547.00mm and 398.44mm, respectively. For annual monthly maximum, the maximum depth at Kemaman, Dungun, Marang, Hulu Terengganu, Kuala Terngganu, Setiu and Besut are, 926.89mm, 826.65mm, 969.77mm, 982.86mm, 1005.00mm, 1079.45mm and 1216.51mm, respectively. Meanwhile, for annual maximum rainfall, the maximum depth at Kemaman, Dungun, Marang, Hulu Terengganu, Kuala Terengganu, Setiu and Besut are 3767.97mm, 4642.43mm, 7065.96mm, 6733.18mm, 6342.88mm, 4707.01mm and 4187.03mm. From Gumble distribution, estimate extreme daily rainfall, probability and return period for 25 years in Kemaman, Dungun, Hulu Terengganu, Marang, Kuala Terengganu, Setiu and Besut are 546.52mm, 556.13mm, 2666mm, 475.4mm, 496.27mm, 551.10mm and 551.10mm. Meanwhile, the return period for 50 years in Kemaman, Dungun, Hulu Terengganu, Marang, Kuala Terengganu, Setiu and Besut are 632.93mm, 623.27mm, 5187.00mm, 545.93mm, 571.61mm, 635.28mm and 635.28mm. Lastly, the return period for 100 years in Kemaman, Dungun, Hulu Terengganu, Marang, Kuala Terengganu, Setiu and Besut are 179.33mm, 730.41mm, 10230.00mm, 616.46mm, 626.95mm, 719.45mm and 719.45mm. Based on the results acquired, every town has a daily estimate extreme rainfall; probability and return period are different. These results may help planning future development